2019
DOI: 10.1186/s12955-019-1092-2
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and quality of life in later life: findings from the health, well-being and aging study (SABE)

Abstract: BackgroundFew studies have specifically investigated the inverse relationship between reduced quality of life in different domains and elevated C-reactive protein (CRP) serum levels in older adults. Therefore, this study investigates the cross-sectional association between quality of life and inflammation in older Brazilian adults.MethodsData were collected from 1255 participants from the third wave (2010) of the Brazilian Health, Well-being and Aging study (SABE), a community-based cohort study of aging. Infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
2
19
2
Order By: Relevance
“…These results might raise the possibility that inflammation in PTSD is involved more in psychological rather than physical aspects of QOL. However, our findings are not in agreement with previous studies that reported significant relationships between inflammation and physical QOL 32,38,42 . This inconsistency may be ascribed to differential measures for assessing QOL between studies, given that the present study used WHOQOL-BREF whereas the previous studies used the 36-item (or 12-item) Short-Form Health Survey (SF-36/SF-12) 32,38,42 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results might raise the possibility that inflammation in PTSD is involved more in psychological rather than physical aspects of QOL. However, our findings are not in agreement with previous studies that reported significant relationships between inflammation and physical QOL 32,38,42 . This inconsistency may be ascribed to differential measures for assessing QOL between studies, given that the present study used WHOQOL-BREF whereas the previous studies used the 36-item (or 12-item) Short-Form Health Survey (SF-36/SF-12) 32,38,42 .…”
Section: Discussioncontrasting
confidence: 99%
“…Various lines of research have demonstrated that elevated inflammation is associated with low psychological resilience 30,31 and QOL 32,33 . Indeed, alterations in the immune/inflammatory system is considered one of the most important biological factors contributing to resilience 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“… 37 Finally, the increased levels of C reactive protein and interleukin-6 due to poor sleep quality have been found to be associated with poor HRQoL. 38 …”
Section: Discussionmentioning
confidence: 99%
“…This might be due to their ability to maintain the balance of the intestinal microbiota, regulate the immunomodulatory responses as well as suppression of the potential pathogens, and the inhibition of carcinogenesis [ 12 , 16 , 17 ]. Since elevated inflammation and oxidative stress are associated with impairment of quality of life [ [20] , [21] , [22] , [23] , [24] ], thus, using synbiotics might be promising in improving the quality of life in patients with BCRL.…”
Section: Introductionmentioning
confidence: 99%